Sources of information used by women during pregnancy and the perceived quality - Maaike Vogels-Broeke; Darie Daemers; Luc Budé; Raymond de Vries; Marianne Nieuwenhuijze (BMC, 2022)
Abstract Background Access to reliable information is critical to women's experience and wellbeing during pregnancy and childbirth. In our information-rich society, women are exposed to a wide range of information sources. The primary objective of this study was to explore women's use of information sources during pregnancy and to examine the perceived usefulness and trustworthiness of these sources. Method A quantitative cross-sectional study of Dutch women's experiences with various information sources during pregnancy, including professional (e.g. healthcare system), and informal sources, divided into conventional (e.g. family or peers) and digital sources (e.g. websites or apps). Exploratory backward stepwise multiple regression was performed to identify associations between the perceived quality of information sources and personal characteristics. Results A total of 1922 pregnant women were included in this study. The most commonly used information sources were midwives (91.5%), family or friends (79.3%), websites (77.9%), and apps (61%). More than 80% of women found professional information sources trustworthy and useful, while digital sources were perceived as less trustworthy and useful. Personal factors explain only a small part of the variation in the perceived quality of information sources. Conclusion Even though digital sources are perceived as less trustworthy and useful than professional and conventional sources, they are among the most commonly used sources of information for pregnant women. To meet the information needs of the contemporary generation of pregnant women it is essential that professionals help in the development of digital information sources.